Assessment of critical factors affecting the performance of trapped field magnets using thin film superconductor tapes. Issue 1 (November 2015) - Selva, Kavita; Li, Xiao-Fen; Majkic, Goran; Masson, Philippe
Abstract: Trapped field magnets have been investigated using Zr-added (Gd, Y)Ba-Cu-O thin film superconductor tapes. Trapped field profiles were examined both experimentally and by simulation over a temperature range of 30 to 77 K. A good match is found between experimental and simulation trapped field data at 77 K and 65 K, but higher trapped field values were obtained experimentally at lower temperatures. Trapped field values up to 1.55 T were measured in an 11 mm thick stack of 55 μm thick superconductor tapes arranged in a crisscross fashion with three tapes per layer. A substantial increase in the trapped field values was found by simulation, in tape stacks made with 20 μm thick tapes. Using such thin tapes, trapped field values of nearly 2 T is predicted in ∼ 13 mm thick tape stacks at 77 K.